Evaluasi Kualitas Layanan Perpustakaan Perguruan Tinggi Masa Pandemi COVID-19 - Badratun Nafis; Syukran Syukran (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional, 2023)
In measuring the service during the pandemic has been provided primely or not. The USK library evaluates these services, one of which is through a customer satisfaction survei. This study aims to measure the extent of user satisfaction with service quality during the COVID-19 pandemic. This study uses a quantitative approach, the data obtained in the form of descriptive statistics. The data collection method is a survei consisting of 5 questions in the form of a Likert scale with a range of 1-5 related to services that can be utilized during a pandemic. The data analysis technique used descriptive analysis method, the data was analyzed by describing the picture based on the data results. Services that are optimized in the midst of a pandemic are online help desk, literature searching services, online book bookings, online fines payments, and online library-free management. The results of the study stated that the users strongly agreed/very good/very satisfied with the quality of the five optimized services during the COVID-19 pandemic. The index value obtained for each service is for online help desk services 92.48%, Literature Searching Service (LSS) services 89.81%, booking book services 92.61%, online fine payment services 87.64%, and the last 90.57% free online library service. The USK library must still provide excellent service both under normal and abnormal conditions such as the COVID-19 pandemic. The USK library must detect the latest “customer focus” trend. This is necessary so that the library can provide services that exceed the expectations of users or beyond their expectations. The results of this study also provide input to the USK Library to always measure the quality of services provided based on the latest trends in the library.